Theoretical Description for Anti-COVID-19 Drug Molnupiravir Electrochemical Determination over the Poly-((1,2,4-triazole)-co-(squaraine dye)) Composite with Cobalt (III) Oxyhydroxide - Tkach, V. V.; Kushnir, M. V.; de Oliveira, S. C.; Shevchenko, I. M.; Odyntsova, V. M.; Omelyanchik, V. M.; Omelyanchik, L. O.; Luganska, O. V.; Kopiika, V. V.; Kormosh, Z. O.; Ivanushko, Y. G.; Kryvetskyi, V. V.; et al. (My University, 2023)
The possibility of electrochemical determination of molnupiravir has been theoretically evaluated for the first time. The molnupiravir electrochemical oxidation over the poly((1,2,4-triazole)-co-(squaraine dye)) composite with cobalt (III) oxyhydroxide has been theoretically evaluated. The correspondent mathematical model analysis has shown that the composite is an efficient electrode modifier for molnupiravir electrochemical determination. As for the oscillatory behavior is more probable than for the simplest case, and its probability will be higher in alkaline media than in neutral.
Шевченко І. М. - https://orcid.org/0000-0002-5985-5092; Одинцова В. М. - https://orcid.org/0000-0002-7883-8917; Омельянчик В. М. - https://orcid.org/0000-0002-3060-7511.
Keywords: COVID-19; molnupiravir; conducting polymers; cobalt (III) oxyhydroxide; triazole; squaraine dye; electrochemical sensor; stable steady-state